Gilteritinib as treatment for extra-medullary relapse of FLT3-ITD acute myeloid leukemia FLT3-ITD, after allogeneic haematopoietic stem cell transplantation - R. Iannotta; M. Celentano; S. Marotta; C.M. Pedata; C. Riccardi; I. Migliaccio; A. Viola; S.M. Muggianu; C. Falco; D Bovenzi; F. Ferrara; A. Picardi (Leukemia Research Reports, 2022)
Case of a patient with acute myeloid leukemia (AML) positive for mutations in both genes NPM1 and FLT3-ITD who underwent two allogeneic haematopoietic stem cell transplants (HSCT); the second allograft one was followed by extramedullary relapse (granulocytic sarcoma of right breast), with blast cells positive for FLT3-ITDmutation.  Treatment with Gilteritinib, a second generation selective oral type I FLT3 inhibitor, was started after the second HSCT with complete regression of breast granulocytic sarcoma in absence of hematological and extra hematologic toxicity. We conclude that Gilteritinib can represent an effective therapy for extra hematologic relapse, with acceptable toxicity and outpatient management.